TEKNIK PENERJEMAHAN PADA PUBLIC SIGN DI BALI SAFARI AND MARINE PARK - Made Sani Damayanthi Muliawan; I Made Astu Mahayana; Jessica Elvira Rosa; Anak Agung Gede Suarjaya (Universitas Warmadewa, 2023)
Bali Safari and Marine Park is a tourist attraction that combines wildlife in its natural habitat with ecosystems that intersect with local culture. With the arrival of tourists to Bali Safari and Marine Park, the availability of public signs (outdoor signs) is an important component in providing the information needed by visitors. Due to the limited media available for outdoor signs (public signs), sentences used in outdoor signs (public signs) are always short and concise, important information is only conveyed in a few words or phrases. This study aims to determine the translation technique used for public signs at Bali Safari and Marine Park. This research is a qualitative descriptive study, with data sources in the form of outdoor signs (public signs) at Bali Safari and Marine Park. The data was obtained through a visual repertoire or photo data in the form of public signs at Bali Safari and Marine Park. Data were analyzed using qualitative-quantitative analysis method. The results will be presented formally in the form of tables and charts to describe the amount of data, as well as informally, namely the results will be described in sentences to make it easier to understand and understand. Keywords: Public sign, translation thecnic, Bali Safari and Marine Park